2019
DOI: 10.1021/acs.jpcc.9b09947
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Dynamics and Ultrasensitive Single-Particle Intermittency in Small-Sized Toxic Metal Free InP-Based Core/Alloy-Shell/Shell Quantum Dots: Excitation Wavelength Dependency Toward Variation of PLQY

Abstract: Observation of strong deviation of photoluminescence excitation curve from absorption curve especially at lower wavelength range, below 450 nm in case of small-sized toxic metal free InP-based corealloy-shell quantum dots, hints toward interesting exciton dynamics. Photoluminescence quantum yield (PLQY) has been observed to be dependent on the excitation wavelength. Monitoring the bleach dynamics employing femtosecond ultrafast pump−probe technique, it could be shown that the rise time increases with decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(77 citation statements)
references
References 71 publications
1
76
0
Order By: Relevance
“…The magnitude of m ON has been found to be ∼1.0 for all λ ex (Table 2), and these values are significantly less in comparison to CdSe (∼1.2) and InP (∼1.2) based CAS QDs. 28,29 The magnitude of m OFF for CsPbBr 3 PQDs (∼1.5−1.7) is however significantly higher in comparison to that of reported optically robust CdSe (∼1.3− 1.4) and InP (∼1.1−1.3) based CAS QDs. 28,29 Thus, CsPbBr 3 PQDs exhibiting higher probability of ON events and lower probability of OFF events are optically superior in comparison to CdSe-and InP-based CAS QDs at the single-particle level.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…The magnitude of m ON has been found to be ∼1.0 for all λ ex (Table 2), and these values are significantly less in comparison to CdSe (∼1.2) and InP (∼1.2) based CAS QDs. 28,29 The magnitude of m OFF for CsPbBr 3 PQDs (∼1.5−1.7) is however significantly higher in comparison to that of reported optically robust CdSe (∼1.3− 1.4) and InP (∼1.1−1.3) based CAS QDs. 28,29 Thus, CsPbBr 3 PQDs exhibiting higher probability of ON events and lower probability of OFF events are optically superior in comparison to CdSe-and InP-based CAS QDs at the single-particle level.…”
mentioning
confidence: 85%
“…28,29 The magnitude of m OFF for CsPbBr 3 PQDs (∼1.5−1.7) is however significantly higher in comparison to that of reported optically robust CdSe (∼1.3− 1.4) and InP (∼1.1−1.3) based CAS QDs. 28,29 Thus, CsPbBr 3 PQDs exhibiting higher probability of ON events and lower probability of OFF events are optically superior in comparison to CdSe-and InP-based CAS QDs at the single-particle level. These observations provide direct evidence of optically inactive mid-gap trap/defect states for PQDs, unlike CdSe/InP QDs.…”
mentioning
confidence: 85%
“…Application of near-unity QY NCs to demonstrating condensed phase laser cooling, however, requires better understanding of how NC QYs are impacted by excitation conditions such as excitation intensity and/or excitation wavelength. The latter is of particular concern given prior studies, suggesting that varying NC excitation energies leads to different emission QYs. Such excitation energy-dependent (EED) emission QYs were first demonstrated by Hoheisel et al who showed through photoluminescence excitation (PLE) measurements that CdSe NC emission QYs decreased monotonically when ensembles were excited to the blue of their band edges. This was rationalized as exciting particles into a continuum of states, distinct from confined NC states.…”
mentioning
confidence: 99%
“…Comparatively lower magnitude of the COV for p values of OFF event distributions (Table ) further confirms that the extent of variation in OFF → ON switching processes is lesser than that of ON → OFF switching processes . ON/OFF event durations are correlated with trapping and detrapping rates. ,, Relatively more disperse ON event distribution as compared to OFF event distribution suggests that trapping rates are broadly distributed in comparison to detrapping rates. This is indeed another very important piece of information which remains masked in the regular PDD analysis of event durations.…”
mentioning
confidence: 63%
“…Blinking dynamics in QDs/PNCs has in general been analyzed employing the histogramming-thresholding (HT) technique, and the probability density distribution (PDD) of ON and OFF event durations has been fitted with different equations (see Supporting Information, p S7). However, cumulative HT analyses of PL blinking dynamical analyses yield only ensemble-averaged information, which is not quite useful to probe ergodicity or statistical aging of the PNC.…”
mentioning
confidence: 99%